Sosio Psikologis Dalam Implementasi Fungsi Seorang Dalang - Padnobo, Halintar Cakra; Nurnani, Dewi (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
This article analyzes the relationship between social-psychology and puppetry, by examining how the five socio psychological elements—attitudes, beliefs, emotions, habits, and desires—influence the character of a dalang and the quality of wayang performances. Based on social psychology theories, this article shows how these elements shape the behavior patterns of a dalang in carrying out his profession and interacting with the audience. The dalang, as the center of a wayang performance, is required to understand and apply these five elements in order to achieve perfection in the performance and to create a harmonious relationship with the audience. The theories used in this article include the basic concepts of general psychology explained by Irwanto et al. (1991), the influence of trust and emotions in social interactions, as described by Sujanto (1993) and Damajanti (2006). Apart from that, the importance of socio-psychology in creating quality art is also highlighted, with. It is hoped that this article can provide deeper insight into the importance of understanding socio-psychology for dalang and audiences in creating meaningful performances.